Talent Management Strategies for The Millennial Generation Workforce: A Systematic Literature Review - Budiman Abdulah (Agregat: Jurnal Ekonomi dan Bisnis, 2025)
This study analyzed 22 documents published between 2017 and 2025, including journals, books, and other publications. The analysis found that the annual growth rate of publications was 0%, indicating stability in the number of publications over the period. The average age of the documents was 5.18 years, indicating that most documents are relatively new, but still include pre-existing references. The average citation rate per document was 6,591, indicating that these documents have significant influence in the scientific community. The method used in this study was Systematic Reviews and Meta-Analyses (PRISMA), which allows for systematic data collection and analysis to identify patterns and trends in the literature. Of the 59 authors involved, only 4 documents were written by a single author, while the average of 2.68 authors per document indicates high collaboration between authors. However, international collaboration only reached 4.545%, indicating limited international engagement on this topic. The most frequently published document type was articles (12 documents), followed by book chapters and conference papers, each with 5 documents. This study provides insight into author contributions, collaborations, and the predominant publication types on this topic. Limitations of this study include the lack of international collaborations that could broaden the scope and diversity of the topics covered